(NvIZNX I TWOR^ESTWO gEGUNI ~IT^QN (B/s - d; d ((NeREWAN (B:s (NaR^E[(B,s, 2003)
(NrEZ(B.: (NARM(B., (NANGL(B.s
(NiZD(B. (NREALIZOWANO BLAGODARQ SPONSORSTWU G(B-(NNA rAFIKA aWETISQNAs
(NpRILOV(B.: (NS(B. 105-153s
(NbIBLIOGR(B. (NW PODSTRO^(B. (NPRIME^(B.s
Keywords: (N~IT^QN(B, (NgEGUNI oGANESOWNAs; (NmUZYKALXNAQ KULXTURAs -- (NaRMENIQs; (NmUZYKOWEDENIEs; (NdEQTELI ARMQNSKOJ KULXTURYs; (NkOMPOZITORY ARMQNSKIEs